4(3x+11)=x(16+4x)

Simple and best practice solution for 4(3x+11)=x(16+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+11)=x(16+4x) equation:


Simplifying
4(3x + 11) = x(16 + 4x)

Reorder the terms:
4(11 + 3x) = x(16 + 4x)
(11 * 4 + 3x * 4) = x(16 + 4x)
(44 + 12x) = x(16 + 4x)
44 + 12x = (16 * x + 4x * x)
44 + 12x = (16x + 4x2)

Solving
44 + 12x = 16x + 4x2

Solving for variable 'x'.

Combine like terms: 12x + -16x = -4x
44 + -4x + -4x2 = 16x + 4x2 + -16x + -4x2

Reorder the terms:
44 + -4x + -4x2 = 16x + -16x + 4x2 + -4x2

Combine like terms: 16x + -16x = 0
44 + -4x + -4x2 = 0 + 4x2 + -4x2
44 + -4x + -4x2 = 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
44 + -4x + -4x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(11 + -1x + -1x2) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(11 + -1x + -1x2)' equal to zero and attempt to solve: Simplifying 11 + -1x + -1x2 = 0 Solving 11 + -1x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -11 + x + x2 = 0 Move the constant term to the right: Add '11' to each side of the equation. -11 + x + 11 + x2 = 0 + 11 Reorder the terms: -11 + 11 + x + x2 = 0 + 11 Combine like terms: -11 + 11 = 0 0 + x + x2 = 0 + 11 x + x2 = 0 + 11 Combine like terms: 0 + 11 = 11 x + x2 = 11 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. + 0.25 + x2 = 11 + 0.25 Combine like terms: + 0.25 = 1.25 1.25 + x2 = 11 + 0.25 Combine like terms: 11 + 0.25 = 11.25 1.25 + x2 = 11.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 11.25 Calculate the square root of the right side: 3.354101966 Break this problem into two subproblems by setting (x + 0.5) equal to 3.354101966 and -3.354101966.

Subproblem 1

x + 0.5 = 3.354101966 Simplifying x + 0.5 = 3.354101966 Reorder the terms: 0.5 + x = 3.354101966 Solving 0.5 + x = 3.354101966 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 3.354101966 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 3.354101966 + -0.5 x = 3.354101966 + -0.5 Combine like terms: 3.354101966 + -0.5 = 2.854101966 x = 2.854101966 Simplifying x = 2.854101966

Subproblem 2

x + 0.5 = -3.354101966 Simplifying x + 0.5 = -3.354101966 Reorder the terms: 0.5 + x = -3.354101966 Solving 0.5 + x = -3.354101966 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -3.354101966 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -3.354101966 + -0.5 x = -3.354101966 + -0.5 Combine like terms: -3.354101966 + -0.5 = -3.854101966 x = -3.854101966 Simplifying x = -3.854101966

Solution

The solution to the problem is based on the solutions from the subproblems. x = {2.854101966, -3.854101966}

Solution

x = {2.854101966, -3.854101966}

See similar equations:

| H=5+10t-5t^2 | | -5h=2/2 | | 14x+6=16x | | 24n^2+6n=0 | | 6n+21=12n+-15 | | 16y+11x=13 | | -8000+1.2(w)+2(x)=0 | | 36(-5/6r) | | 12x-8=161 | | Y-6=3(x-8) | | 10=-8m/4 | | Cos^2x-5sin-5=0 | | x^3+3x^2-28x-5304=0 | | -8000+1.2(x)+2(w)=0 | | 5/2x-5=-5 | | 6x^2+6x+8=0 | | 11=2/3x | | 3x+11-7x-14=5+2x+4x+2 | | 1/2secx-1=0 | | 12.88-.88(x+.5)=.25x+2(x-3.17) | | -8000+2(w)+1.2(x)=0 | | 6x^3-14x^2+8x-2240=0 | | 5(5x-5)+8=-6(-3x+4) | | ln(x-3)+ln(x+5)=0 | | 18÷9/67 | | y=-150+500 | | (7+I)(4-9i)=0 | | 8x+4(4x+3)=4(6x+4)-3 | | (-5000+(0.5(w))+(.8(x)))*.5(w)=(0)*.5(w) | | ((x^2/3)(y^-4/5))^1/2 | | 8+2y=-18 | | 5x+8=.5(4x+1+x) |

Equations solver categories